Frequency Stability and Control in Island Operation Using Wind Power - Eriksson, Markus (My University, 2024)
Abstract An Increased frequency of extreme weather events and concerns of attacks has caused a growing interest in island operation for parts of a power system to increase its resilience. Island operation constitutes designing part of the power system as an island system, able to disconnect from the larger grid and independently sustain its loads. Wind power is also becoming increasingly important for the power system as decarbonizing efforts are made. Wind power does however have an intermittent power production and a detrimental effect on power system inertia. These challenges with wind power raise uncertainties regarding what role it can serve within island systems and still maintain the island stability. Simulations have therefore been conducted in MATLAB/Simulink and in PSS/E to address these uncertainties. The simulations are conducted to evaluate how the stability of a wind and hydro based island system changes when the wind power within the island provides frequency control. The stability was analyzed during transition from grid connected to island operation and during the continued operation thereafter. The MATLAB/Simulink simulations were conducted to design the wind turbine control and the strategies used for the wind power frequency control. Two wind power frequency control strategies were implemented. The first is inertia emulation, where the synchronous inertial power response to a frequency change is emulated for the wind turbine. The second strategy implemented is droop control while derating the turbine, where the wind turbine’s power is purposely reduced to create a power reserve that is utilized for controlling the frequency. The design wind turbine control was then converted to PSS/E using user defined models and applied to a simple test network for island operation. The simulations of the island test network showed that using wind power inertia emulation caused frequency stability improvements for the frequency for all cases analyzed. This frequency stability improvement could be further improved by also including wind power droop control. However, using droop control up-regulation of the frequency comes at the cost of reduced wind power production, as it is necessary to create a power reserve for this method. The frequency improvements from the wind power frequency control for the transition from grid connected to island operation were especially significant. The wind power frequency control also showed an improvement for the voltage stability in the test network. The stability improvements indicate that wind power frequency control can reduce the requirements on the wind power penetration and on the possible power transfer between the island system and the grid when grid connected.
Keywords: Keywords: Island operation, Frequency control, Wind power control, Inertia emulation, Wind power de-rating